Increase by adrenaline or angiotensin II of the accumulation of low density lipoprotein and fibrinogen by aortic walls in unrestrained conscious rats. - Cardona-Sanclemente, L. E. (1996)
1. Earlier experiments of ours with anaesthetized rabbits showed that infusions of catecholamines into the carotoid blood stream significantly increased the uptake of radioiodinated low density lipoprotein (LDL) by the artery wall after as little as 2 h. This observation has now been extended to much longer time periods, i.e., 6 days, and another species, viz. conscious and unrestrained rats; also to another pressor agent, angiotensin II, as well as to another plasma protein, fibrinogen. 2. Groups of rats were infused from subcutaneously implanted osmotic minipumps for 6 days. The infusions were either into a carotid artery or into the surrounding tissues, with essentially the same effects. Control animals were infused with saline, and test animals with either adrenaline or angiotensin II. The minipump concentration of adrenaline of 4-5 microM, which gave blood concentrations of 25-41 nM, increased the blood pressure significantly after 3 days. The minipump concentration of angiotensin II of 9.9 mg ml-1 was chosen to produce similar increases in blood pressure. 3. Five days after starting the infusion, rats were injected i.v. with either homologous or human LDL labelled with [125I]-tyramine cellobiose (TC), or with [131I]-TC labelled human fibrinogen. Twenty-four hours later, the animals were killed and the radioactivities determined in the whole aorta. The labelled TC radioactivities represent primarily metabolised protein (because TC is trapped intracellularly), but also include the fraction of intact, i.e., non-metabolized protein in transit through the vessel wall. To determine the contribution of the latter, in some experiments we injected double-labelled [131I]-[125TC]-LDL only. These experiments showed that the [131I]-LDL counts representing protein in transit accounted for approx. 20% of the total 125TC counts, and that this percentage was not significantly affected by adrenaline or angiotensin II. Therefore, the bulk of the experiments was carried out with single labelled proteins, using 125I to label TC-LDL and 131I to label TC-fibrinogen. In these experiments, the radioactivity of the arterial wall thus provides a cumulative measure of the uptake and degradation of proteins. 4. Aortic wall radioactivities from rat and human LDL and from human fibrinogen were significantly increased by both agents. Adrenaline at 25-41 nM increased the radioactivities by 52 and 47% for rat and human LDL respectively, and by 31% for human fibrinogen; these differences were highly significant (P < 0.01). Angiotensin II at ca. 10 nM also increased the radioactivities significantly, by 21% for human LDL and by 109% for human fibrinogen (P < 0.05). 5. The results suggest that the accumulation of LDL and of fibrinogen by rat aorta is increased by adrenaline or by angiotensin II at concentrations which raise the blood pressure progressively and significantly after 3 or 5 days respectively.